Trilogi Kekerasan dalam Perjanjian Lama: Membongkar Pemahaman Umat Beriman tentang Kekerasan Manusia, Kekerasan Ilahi, dan Kekerasan Doa - Loba, Klementius Anselmus; Nainggolan, Silvana Natalia; Gale, Stefanus; Tanureja, Indra (KAMASEAN: Jurnal Teologi Kristen, 2023)
Religion and violence have long been linked. In Christianity, the presence of violent texts in the Bible, especially in the Old Testament, further exacerbates this situation. The Old Testament texts include three types of violence: human violence against humans, violence perpetrated by God, and human appeals to God for violence. This legacy of biblical violence creates theological and ethical challenges for those who seek spiritual and ethical guidance from the Bible. This paper aims to examine the responses or views of the faithful, who have no formal education in the Bible, towards violent texts in the Old Testament. The research method used is qualitative, with a field study and a literature study approach. Interviews were conducted with informants to explore their understanding of the biblical texts of violence, and the findings will be confronted with expert explanations through a literature study. The resource persons in this study are parishioners of St. Agata-Parish of Maria Assumpta Pakem, Yogyakarta, with various educational backgrounds. The results of this study attempt to present theological and ethical ways of understanding violent texts so that the faithful can gain a more balanced and contextual understanding of these texts. By exploring people's understanding of violent texts in the Old Testament, this research contributes to understanding the complexities and challenges faced by the faithful in reading and understanding the Bible.